Catalog and distribution atlas of the Scarabaeoidea (Insecta: Coleoptera) of El Salvador - José D. Pablo Cea; Ronald D. Cave; Francisco A. Serrano-Peraza; Raquel Alvarado-Larios; Cuauhtémoc Deloya; Katerin A. Serrano-Chicas; Elizabeth Alfaro; Abizai C. Chinchilla-Rodríguez; Daniel Girón-Segovia; Jorge Ari Noriega (Revista Mexicana de Biodiversidad)
Less than 1% of the literature on El Salvador’s biodiversity is about terrestrial invertebrates, which limits our knowledge of this group’s diversity, richness, and distribution in the territory. Scarabaeoidea are megadiverse in multiple ecosystems and perform many functions. This work aims to catalog the Scarabaeoidea in El Salvador. We conducted an exhaustive review of published literature and reviewed numerous entomological collections with relevant material. Maps were constructed to visualize the known distribution of each species in the country. There are 295 scarab beetle species (including 19 new country records) representing 106 genera in 7 families in El Salvador. Six precinctive species are known. Twenty-two species are discarded as occurring in El Salvador, either because they are not valid species or because of misidentifications or dubious records. This work is the first approach to knowing the Scarabaeoidea in El Salvador, a territory that is usually considered of no importance for the conservation of regional biodiversity due to its small area, high rate of deforestation, and overpopulation. The results of this work reinforce the need for biological prospecting in the territory to know, conserve, and protect the remaining biodiversity.